Preserving cognitive function in patients with Alzheimer's disease: The Alzheimer's disease neuroprotection research initiative (ADNRI) - Liu, Jie (2023)
The global trend toward aging populations has resulted in an increase in the occurrence of Alzheimer's disease (AD) and associated socio-economic burdens. Abnormal metabolism of amyloidâ Î² (AÎ²) has been proposed as a signiï¬ cant pathomechanism in AD, supported by results of recent clinical trials using antiâ AÎ² antibodies. Nonetheless, the cognitive beneï¬ ts of the current treatments are limited. The etiology of AD is multifactorial, encompassing AÎ² and tau accumulation, neuroinï¬ ammation, demyelination, vascular dysfunction, and comorbidities, which collectively lead to widespread neurodegeneration in the brain and cognitive impairment. Hence, solely removing AÎ² from the brain may be insufï¬ cient to combat neurodegeneration and preserve cognition. To attain effective treatment for AD, it is necessary to (1) conduct extensive research on various mechanisms that cause neurodegeneration, including advances in neuroimaging techniques for earlier detection and a more precise characterization of molecular events at scales ranging from cellular to the full system level; (2) identify neuroprotective intervention targets against different neurodegeneration mechanisms; and (3) discover novel and optimal combinations of neuroprotective intervention strategies to maintain cognitive function in AD patients. The Alzheimer's Disease Neuroprotection Research Initiative's objective is to facilitate coordinated, multidisciplinary efforts to develop systemic neuroprotective strategies to combat AD. The aim is to achieve mitigation of the full spectrum of pathological processes underlying AD, with the goal of halting or even reversing cognitive decline.